Statistics by statistician: Importance in education / Nor Habibah Tarmuji and Sharifah Norhuda Syed Wahid - Tarmuji, Nor Habibah; Syed Wahid, Sharifah Norhuda (2013)
Statistics is an incredibly useful course and becomes an important part of life. Confidence theory, null hypothesis, odds or likelihood and also research shows that there is almost no end to the significance of statistics. The importance of statistics is great because it provides detailed information about situations. But currently many fields have abused the statisticians in many ways such as eliminate the statistical courses in their program structure. Therefore this study is conducted to determine the statisticians' role especially in higher learning education level. Findings from selected higher learning institution revealed that there is a significance difference in learning and teaching process between taught by statistician and non-statistician who is statistician was better. Statistician more efficient because 48.78 percent of students got excellent result compared for those taught by non statistician with only 10.17 percent. It shows that statistician can attract student to enjoy learning statistics. Hopefully this study can provide useful information for everybody about the importance of statistics in education and the role of statisticians in statistics course.